Process modeling of syngas conversion to ethanol and acetic acid via the production of dimethyl ether and its carbonylation - Kim, Seungwoo; Jung, Hyun Seung; Lee, Won Bo; Bae, Jong Wook; Park, Myung-June (The Korean journal of chemical engineering, 2022)
A process model was developed to simulate the generation of ethanol or acetic acid by selectively using syngas from coke oven gas as the carbon source. The simulation involved three reactors: the first reactor converts syngas into dimethyl ether over a hybrid Cu/ZnO/Al 2 O 3 /ferrierite catalyst; in the second reactor, carbonylation of dimethyl ether to methyl acetate takes place. The kinetic parameters for the carbonylation reaction were estimated by fitting the model to the experimental results. The third reactor uses the hydrogenation or hydrolysis of the methyl acetate to selectively synthesize ethanol or acetic acid, respectively. In the integrated process, a recycling loop was introduced, and its effects on the conversion, carbon molar yield, energy consumption, and capital and utility costs were evaluated. The results show that the recycling loop could enhance the carbon molar yield by approximately 20 times compared to that in the open-loop case owing to the high overall conversion (91–97%) of dimethyl ether in the second reactor.